USAHA SARANG BURUNG WALET DI DESA BATU BALAI KECAMATAN MUARA BENGKAL KABUPATEN KUTAI TIMUR - Rusmiyati, Rusmiyati -; Dewi, Indah Novita; Istikomah, Istikomah; Nur Abdi, Muh Angga (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to determine the income, profit level and BEP of swallow nest business in Batu Balai Village, Muara Bengkal District. Data collection methods were carried out through observation and interviews with questionnaire tools. The sample was determined by the characteristics of swallow breeders who had been breeding for 5 years, so the sampling technique used was proportional sampling. With this sampling technique, there were 20 swallow farmer respondents in Batu Balai Village. The results showed that swallow nest production in Batu Balai Village was 42.3 kg/month. With this amount of production, revenue of Rp. 3,553,200,000 was obtained, with an average of Rp. 177,660,000 per breeder per year. Swallow nest business income in Batu Balai Village is Rp.1,955,700,144,-/year with an average income of Rp.97,785,007,-/year for each breeder. As for the R / C ratio analysis of 9.86, the swallow nest business is feasible to be cultivated because the R / C value is more than 1 declared profitable. The production BEP of swallow nest business is 1.97 kg while the unit BEP is Rp. 13,790,000, - this shows that the swallow nest business in Batu Balai Village is profitable